(untitled) (Northampton, MA, 2006)
"Poverty Strategies in Asia" is an examination of a wide range of measures aimed at reducing poverty in the region. It is widely recognized that while high and sustained economic growth is critical for poverty reduction, there are other policy interventions that may also be significant in a 'growth plus' approach to poverty reduction. This volume brings together a series of case studies on the poverty impact of alternative interventions in a broad range of Asian economies. The measures examined within the book cover trade liberalization both in general and in a specific market, infrastructure investment (particularly in roads), population policies, cash transfers, microfinance, employment guarantee programs and contract farming. The countries covered include the Philippines, Lao PDR, Pakistan, India and Thailand. While the results illustrated by the contributors are mixed, they demonstrate the potential for further progress in poverty reduction. This latest joint publication by the ADBI and Edward Elgar Publishing will be warmly welcomed by scholars and researchers of Asian studies and development.
Keywords: Nghèo nàn,Poverty; Châu Á,Asia